PRISON MOTHERS: WISHES AND WOUNDED WORDS - Mendes Braga, Ana Gabriela [UNESP]; Pereira, Jessica Xavier [UNESP] (Univ Estado Rio Janeiro, 2020)
The present paper is the result of the research Imprisoned maternities and free mothers: access to justice and the rights of women prisoners, which aimed to reflect justice from the perceptions and experiences of mother's arrest in the state of Sao Paulo after the implementation of the Early Childhood Act in Brazil (no 13.257/16). Based on the qualitative approach, 106 interviews were carried out at the Women's Penitentiary of Pirajui in the context of the collective mobilization Free Mothers, a project carried out by the Institute for the Defense of the Right of Defense (IDDD). This text focuses on words and wishes unspoken in custody: what they wanted to say to the judge of the case and the alternatives that they themselves envision for their arrestment. In the end, we concluded that, while the protection of exercising maternity expands for women in prison, the path of access to justice is still being paved. As imprisoned mothers tell us, there are discourses and practices in the justice system that, paradoxically, prevents the access to justice and especially the right to exercise maternity outside of prison, guaranteed by law and reaffirmed by the Brazilian Supreme Court.
Keywords: female incarceration; access to justice; maternity; narratives; Early Childhood Act